Knowing Women : Same-Sex Intimacy, Gender, and Identity in Postcolonial Ghana - Dankwa, Serena Owusua (Cambridge : Cambridge University Press, 2021)
Knowing Women is a study of same-sex desire in West Africa, which explores the lives and friendships of working-class women in southern Ghana who are intimately involved with each other. Based on in-depth research of the life histories of women in the region, Serena O. Dankwa highlights the vibrancy of everyday same-sex intimacies that have not been captured in a globally pervasive language of sexual identity. Paying close attention to the women's practices of self-reference, Dankwa refers to them as'knowing women' in a way that both distinguishes them from, and relates them to categories such as lesbian or supi, a Ghanaian term for female friend. In doing so, this study is not only a significant contribution to the field of global queer studies in which both women and Africa have been underrepresented, but a starting point to further theorize the relation between gender, kinship, and sexuality that is key to queer, feminist, and postcolonial theories. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 02 Dec 2020).